2013
DOI: 10.4028/www.scientific.net/amm.432.32
|View full text |Cite
|
Sign up to set email alerts
|

A DSC Investigation of the Effects of Cold Deformation and Low Temperatures Aging on the Microstructural Stability of a Peak Aged (PA) Al 6061 Alloy

Abstract: The effects of cold deformation and low temperature aging on the microstructural stability of a peak aged (PA) Al 6061 alloy were investigated by means of DSC and microhardness measurements. During aging at a relatively low temperature (100 °C) of the PA material, a small increasing of the mechanical properties was detected, which was explained by the formation of atomic clusters, GP zones and β phase. The response to the aging treatment of the cold deformed materials depends on both the level of the cold defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The dissolution peak of both β" and β' occurred at the range of 340-400 °C (peak 4) and the formation and dissolution of equilibrium β phase occur at the temperature ranges [400-455 °C] (peak 5) and [455-505 °C] (peak 6) respectively. Interpretation of all reaction peaks has been made on the basis of The DSC thermogram of the ST and cold rolled sample, shows the occurrence of almost the same precipitation and dissolution reactions, however, one can state that cold rolling has introduced the following effects : -The displacement of all reactions towards low temperatures; this is due to the enhanced diffusion rate of solute atoms, because of the high density of dislocations, which promote the occurrence of all reactions at relatively low temperatures [11,16,17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dissolution peak of both β" and β' occurred at the range of 340-400 °C (peak 4) and the formation and dissolution of equilibrium β phase occur at the temperature ranges [400-455 °C] (peak 5) and [455-505 °C] (peak 6) respectively. Interpretation of all reaction peaks has been made on the basis of The DSC thermogram of the ST and cold rolled sample, shows the occurrence of almost the same precipitation and dissolution reactions, however, one can state that cold rolling has introduced the following effects : -The displacement of all reactions towards low temperatures; this is due to the enhanced diffusion rate of solute atoms, because of the high density of dislocations, which promote the occurrence of all reactions at relatively low temperatures [11,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…-The reduction of clusters/GP zones formed amount, which is mainly due to the fact that the clustering of solute atoms in solid solution at the early stage of phase decomposition is significantly influenced by the vacancy concentration [2 -4]. As dislocations are sinks for excess vacancies, the density of vacancies in the alloy decreases as dislocations are created during cold rolling [17]. It is also observed that the endothermic effect related to atomic clusters/GP zones dissolution is clearly composed of two small endothermic peaks which can be explained by the dissolution of two kinds of atomic clusters/GP zones; those formed during heating in the DSC apparatus (the first one) and those formed before DSC test (the last peak).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their dissolution is recognised by the endothermic peak B 2 situated around 433 K. For CR sample, we note that the formation of GP zones (A 1 ) is happening during the experiments and not before CR, since the heavy plastic deformation suppresses their formation [12,13] while their dissolution is not detected on DSC. Moreover, the exothermic peak C 1 (around 503 K) is attributed to the precipitation of β′, since the plastic deformation promotes its heterogeneously distributed formation due to short-circuit provided by dislocation tangles [17]. On the derivative dilatometric curve in the same interval, a contraction (3) is observed.…”
Section: Resultsmentioning
confidence: 99%
“…The plastic deformation can be used to improve the ageing process since its effects are remarkable due to introduced defects. The plastic deformation before final age hardening can change the precipitation sequence, since the dislocations provide heterogeneous nucleation sites for the precipitates [12][13][14][15][16][17][18], by the suppression of GP zones [12,13] and β precipitates [13][14][15][16][17][18], as well as accelerating the precipitation kinetics [13][14][15][16][17][18]. The nucleation and growth of the intermediate phases are accelerated and the stable phase is precipitated at dislocations [12][13][14][15][16][17][18], as it was suggested that the increased density of defects in the crystal structure would enhance appreciably the diffusion distance of Si and hence promote the formation of more Si-rich particles [19].…”
Section: Introductionmentioning
confidence: 99%